Dealing with Hajj costs: the challenges - Mohd Said, Ridzwana; Senik, Rosmila (Universiti Putra Malaysia Press, 2014)
The case is about the unavoidable increasing Total Hajj Costs borne by Tabung Haji (TH) Malaysia due to physical development in Makkah and improvement of Hajj services. It has been a long practice by TH to charge Hajj pilgrims at a fixed amount (Hajj Payment) for series of years and sponsor the remaining of the Hajj Cost (Hajj Costs Obligation). TH is not the sole party in determining the Hajj Payment. Any changes need consent of government, particularly the Prime Minister’s office. The implication is TH would bear an increasing Hajj cost obligation. This case gives opportunity to readers to analyse the financial performance of TH using ratio analysis, evaluate the payment scheme of Hajj costs and recommend reasonable strategies on Hajj Costs Scheme without sacrificing the philosophy of TH establishment.